Faktor Determinan Infeksi Menular Seksual Dan HIV/AIDS Di Puskesmas Ibrahim Adjie Kota Bandung Tahun 2022 - Rosita Rosita; Yanti Herawati; Ira Kartika; Oktarina Sri Iriani; Dyah Triwidiyantari; Dian Purnama Sari (Jurnal Medika Nusantara, 2023)
Sexually transmitted infections (STIs) are diseases that have a major impact on sexual and reproductive health. The city of Bandung is the 3 regencies/cities with the most STI cases in West Java where from 2021 there has been an increase in the number of cases from 29.7% or 2,057 cases in 2022. Meanwhile, the cumulative HIV/AIDS cases until the end of 2022 reached 2,428 people. The aim of this research is to determine the determinant factors for the incidence of sexually transmitted infections and the incidence of HIV/AIDS at the Ibrahim Adjie Community Health Center, Bandung City in 2022. The research design uses a cross sectional study, the variables studied are sexually transmitted infections, HIV/AIDS, age, risk factor groups. condom use, and number of sexual partners. Data analysis was carried out univariate, bivariate and multivariate using linear regression analysis techniques. The results of the study show that there is a significant relationship between infectious infections and HIV based on age, risk factor groups, condom use. Multivariate test based on sexually transmitted infection variables, of the four determinant factors, only the risk factor group has an influence on sexually transmitted infections. Meanwhile, from the HIV variable, of the four determinant factors, there are 3 factors that influence the incidence of HIV, namely risk factor groups, number of sexual partners, and condom use.